IMPACT OF NUTRITION ON GROWTH AND INSECT INFESTATIONS ON KAGZI LIME IN RESPECT OF MANAGEMENT OF CITRUS DECLINE - SHARMA, S.K.; CHAVAN, V.M.; DHALE, M.G. (Annals of Agricultural Research, 2014)
Different combinations of macro-nutrients were applied, viz, T1 (Control) – zero doses of nitrogen (N), phosphorus (P2O5) and potassium (K2O); T2—125 g N, 30 g P2O5 and 70 g K2O per year per plant, T3 (optimum doses) —150 g N, 40 g P2O5 and 80 g K2O per tree per year, and T4 — 175 g N, 50 g P2O5, and 90 g K2O per year. Till the second years of plant age, growth was not affected significantly by nutrition, indicating adequate availability of these nutrients in the soil. However, in the third year, macro-nutrients had significant effect on plant growth. Differences in plant height between T1 and T2/T3 T4 were significant, i.e., all nutrient combinations showed significantly higher plant height over the control. Differences in collar diameter between T1 and T4, and between T2 and T4 were  significant. Micronutrient application increased collar diameter significantly. The highest incidence of citrus leaf miner (Phyllocnistis citrinell Sta.) was observed on the plants under T4 whereas the incidence was lowest (29.76%) in T1. Average population of aphids was maximum in December- January, while the minimum was in March to May. The incidence of CTV or citrus decline was not visible in any of the treatment combinations.